Physical, verbal, and indirect aggression: Gender differences - Žukauskienė, Rita (Psichologija, 1999)
Gender differences regarding aggressive behaviour were investigated in 154 school children three age cohorts: 8-9, 11-12, 13-14-year-olds through peer rating technique DIAS (Lagerspetz, Björkqvist, 1992, Björkqvist, Österman, Kaukiainen, 1992).The principal finding was that girls made greater use of indirect means of aggression, whereas the boys tended to employ direct means of physical and verbal aggression. Indirect aggressive strategies were not fully developed among the 8-9 boys and girls, but they were already prominent among the 11-12 boys and girls, and much more developed among the 13-14 years-old girls.
Keywords: physical; verbal; indirect aggression; aggression